Survey of the Ethiopian linyphiid spider fauna. I. Subfamily Erigoninae (Arachnida, Araneae, Linyphiidae) - Tanasevitch, Andrei V. (Zootaxa, 2023)
Eight identifiable species of the linyphiid spider subfamily Erigoninae have been reviled from the Oromia Region, Ethiopia, seven of which being described as new: Callitrichia asela n. sp. (♂, ♀), Callitrichia protegularis n. sp. (♂, ♀), Microcyba magna n. sp. (♂, ♀), Microcyba oromia n. sp. (♂, ♀), Pelecopsis arsi n. sp. (♂, ♀), Savignia ericola n. sp. (♂), and Walckenaeria (Tigellinus) trivialis n. sp. (♂, ♀). The cosmopolitan Ostearius melanopygius (O. Pickard-Cambridge, 1880) is reported from Ethiopia for the first time.